The Use of Listen - Read – Discuss strategy to Improve Students Reading Comprehension - Arie Pawestri Regita Cahyani; Sri Handayani (English Education Department Slamet Riyadi University Surakarta, 2020)
The research aims: (1) to know how can Listen Read Discuss strategy implemented effectively in improving the students’ reading comprehension at 8th Grade Student of SMP N 1 Colomadu in the academic year of 2019/2020, and (2) to know how far the improvement the students reading comprehension using Listen Read Discuss Strategy at 8th Grade Student of SMP N 1 Colomadu in the academic year of 2019/2020. The researcher conducted a classroom action research at the eighth grade of SMP N 1 Colomadu from September to November 2020. This research was conducted in class VIII D which consisted of 31 students with 17 boys and 14 girls. The research concerned in improving students’ reading comprehension on narrative texts using Lisen Read Discuss Strategy. The research consisted of two cycles. The procedure of action research consisted of planning, implementation of the action, observation, and reflection. In collecting the data, the researcher used observation, interview and document. In analyzing the data, the researcher used quantitative and qualitative data analysis. The result of this research showed that Listen Read Discuss strategy can improve students’ reading comprehension on narrative texts at eighth grade of SMP N 1 Colomadu. The improvement can be seen from the result of the test. It was 63.96 in pre-test, then it became 74.83 in post-test 1 and it became higher in post-test 2 (80.32). The result of post-test 1 and post-test 2 were higher than the minimum score KKM in that school which was 75.0. Besides, the student participated actively in teaching and learning process. From the result above, it can be concluded that Listen Read Discuss (LRD) Strategy can improve students’ reading comprehension at the eighth grade of SMP N 1 Colomadu. Keywords: Classroom Action Research, Listen Read Discuss (LRD) Strategy, Reading Comprehension.